2008
DOI: 10.12973/ejmste/75364
|View full text |Cite
|
Sign up to set email alerts
|

Constructivism and Peer Collaboration in Elementary Mathematics Education: The Connection to Epistemology

Abstract: In this paper, an attempt is made to determine if peer collaboration increases student achievement in teaching elementary mathematics. Empirical evidence and philosophical problems with constructivist epistemology are considered. Two things are argued: first, it is reasonable to think, for elementary mathematics, peers collaboration is useful (especially in heterogeneous groups). Peer collaboration is an appendage to instruction, not a replacement for the didactics of an expert, or individual problem solving (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 7 publications
0
9
0
1
Order By: Relevance
“…Some applications include immediate and ongoing assessment (Eisele-Dyrli, 2011), digital game-based learning (Aslan, 2011;Saridaki, Gouscos and Meimaris, 2010), and construction of meaningful mathematical knowledge in real situations (Carr, 2012). Gupta (2008) supported that learning with handheld mathematical manipulatives encourages students to explore new mathematical material in a discovery mode that is in line with the principles of constructivism. Various research studies have shown that mathematical manipulatives, such as the Hands-On Equations learning module, have a positive impact on student learning and retention of mathematical concepts (Jimenez, 2011;Brown, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Some applications include immediate and ongoing assessment (Eisele-Dyrli, 2011), digital game-based learning (Aslan, 2011;Saridaki, Gouscos and Meimaris, 2010), and construction of meaningful mathematical knowledge in real situations (Carr, 2012). Gupta (2008) supported that learning with handheld mathematical manipulatives encourages students to explore new mathematical material in a discovery mode that is in line with the principles of constructivism. Various research studies have shown that mathematical manipulatives, such as the Hands-On Equations learning module, have a positive impact on student learning and retention of mathematical concepts (Jimenez, 2011;Brown, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The constructivist's theory includes learning through discovery, technology, visual teaching aids, and hands-on manipulatives and also includes the idea that using peer collaboration and cooperative learning alone does not produce significant increases in academic performance (Gupta, 2008). The constructivist classroom supports peer collaboration and cooperative learning in combination with one-on-one interaction between the student and the teacher (Walshaw, 2013).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…Secara umum konstruktivisme yaitu mendorong kolaborasi, kegiatan penduhuluan dan eksplorasi, dan menekankan pemecahan masalah otentik (Gupta, 2008). Seiring berjalannya waktu saat ini berkembang E-Learning.…”
Section: Pendahuluanunclassified